Pelatihan Mikrotik Dasar Pada SMK Pawiyatan Surabaya - Weny Indah Kusumawati; Musayyanah Musayyanah; Pauladie Susanto; Charisma Dimas Affandi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Vocation Senior Shcool students who are ready to penetrate industrial company must have hard skills. One of hard skills is being able to use the latest technology, especially network-based technology, namely Mikrotik. Mikrotik is a network devic that can perform as router or access point. With GUI-based application, learning Mikrotik was simple and easy to be applied. The purpose of this training is to equip students to be able to use Mikrotik independently on small-scale networks. This training was held four times, which was attended by 14 student participants and 2 teachers of SMK Pawiyatan Surabaya. The training was held in a computer network laboratory, which consisted of 16 computers as hosts and 16 microphones. Each participant operates Mikrotik independently, guided by the trainer. Training questionnaires were distributed to all participants as an indicator of the success this training. The questionnaire contains training materials, trainer performance, training facilities and training atmosphere. Based on the numbers that have been processed, the average questionnaire rating is 56% strongly agree, 42% agree, and 2% disagree. The assessment of these numbers shows that this PKM activity received a good response from the training participants.